1997
DOI: 10.1093/jac/39.6.757
|View full text |Cite
|
Sign up to set email alerts
|

Quinolone-resistance mutations in the topoisomerase IV parC gene of Acinetobacter baumannii

Abstract: Mutations in the parC gene, which encodes a subunit of topoisomerase IV, were determined in 21 epidemiologically unrelated clinical isolates of Acinetobacter baumannii. Our studies highlight the conserved sequences in the quinolone-resistance-determining region of the parC gene from A. baumannii and other bacteria. Nine of ten isolates with MICs of ciprofloxacin of > or = 32 mg/L showed a change of Ser80 to Leu and one showed a change of Glu84 to Lys. These results suggest that ParC from A. baumannii is a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
119
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(144 citation statements)
references
References 37 publications
18
119
1
6
Order By: Relevance
“…Sequencing results (Table 3) showed that all the A. baumannii clinical isolates from Los Angeles County had a point mutation on the gyrA gene that converted the serine at position 83 (Ser-83) to leucine (Leu) in GyrA, a change that is consistent with a fluoroquinolone-resistant phenotype. No additional amino acid sequence changes were observed for the GyrA polypeptide in these clinical isolates, not even at other "hot spot" amino acid positions (Gly-81, Ala-84, (48). Effects of efflux pump inhibitors on ciprofloxacin resistance.…”
Section: Susceptibility Testing Mics Were Determined For the Panel Omentioning
confidence: 82%
See 2 more Smart Citations
“…Sequencing results (Table 3) showed that all the A. baumannii clinical isolates from Los Angeles County had a point mutation on the gyrA gene that converted the serine at position 83 (Ser-83) to leucine (Leu) in GyrA, a change that is consistent with a fluoroquinolone-resistant phenotype. No additional amino acid sequence changes were observed for the GyrA polypeptide in these clinical isolates, not even at other "hot spot" amino acid positions (Gly-81, Ala-84, (48). Effects of efflux pump inhibitors on ciprofloxacin resistance.…”
Section: Susceptibility Testing Mics Were Determined For the Panel Omentioning
confidence: 82%
“…Specifically, amino acid substitutions at certain positions in subunits A (GyrA and ParC) of both DNA gyrase and DNA topoisomerase IV, due to point mutations in the QRDRs of the genes encoding these two polypeptides, have been found to contribute to fluoroquinolone resistance. In A. baumannii, the most frequent amino acid substitutions occur at position 83 (Ser-83) of GyrA (20,49,52) and at position 80 (Ser-80) of ParC (20,48,52). While changes in GyrA are necessary for moderate levels of fluoroquinolone resistance among clinical isolates of A. baumannii, concurrent modifications in the ParC polypeptide are required in order to achieve high levels of fluoroquinolone resistance (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in contrast to the steric-blocker oligonucleotides, RNase H-dependent oligonucleotides, such as phosphorothioate oligonucleotides, can inhibit protein expression when targeted to widely separated areas in the coding region. [18][19][20] Mechanisms in fluoroquinolone resistance of E. coli fall into two principal categories: alterations in drug targets (for example DNA gyrase or topoisomerase IV) [21][22][23][24][25][26] and decreased cellular accumulation of quinolones. The latter involves the major and constitutively expressed multi-drug efflux pump, AcrAB-TolC.…”
Section: Discussionmentioning
confidence: 99%
“…가장 중요한 돌연변이는 quinolone resistance-determining region (QRDR)이라 불리는 GyrA와 ParC의 특정 위치에서 발생하며, 주로 GyrA의 83번째와 ParC 의 80번째 코돈에서 치환이 발생한다 [16,17]. GyrA의 추가적인 돌연변이는 Gly81, Ala84, Glu87로 알려져 있으며, 이들 돌연 변이로 인해 quinolone계 항균제에 내성을 유도하며, ParC의 경우는 Gly78과 Glu84의 아미노산 치환이 Ser83과 Ser80과 같 이 확인되는 경우에는 quinolone에 높은 수준의 농도에서까지 내성을 유발하는 것으로 알려져 있다 [18,19].…”
Section: Introductionunclassified